Alkali field strength effects on optical, dielectric, and conducting properties of calcium borosilicate glasses. Issue 2 (15th January 2023) - Bansal, Neetu; Khan, Savidh; Sharma, Gaurav; Rajni,; Kumar, Devender; Singh, K.
Abstract: This paper reports the alkali field strength effect on structural, optical, dielectric, and conducting properties of calcium borosilicate glasses. Glass compositions 60SiO2 –5B2 O3 –15CaO-20R2 O (where R = Li, Na, K) are synthesized by melt-quench technique. The density shows an increasing trend with the increasing atomic weight of substituted alkali metal oxides. On the other hand, the hardness and elastic modulus are found to decrease from Li2 O to K2 O. The tendency of oxide ions to donate electrons is found to increase with decreasing field strength of alkali ions in the glass. The optical band gap of glasses is found in the insulating range, i.e. 4.27 eV–4.38 eV. The diffusion coefficient and conductivity of Li2 O-containing glass is the highest followed by Na2 O and K2 O. Present synthesized glasses are found to be suitable for use as a substrate in thin film solar cells.